FINANCIAL LITERACY EDUCATION A KEY TO COMBATING HOUSEHOLD DEBT - Zega, Neill Ayu Moralina; Octafian, Ray (Penelitian dan Pengembangan Ilmu, 2025)
Increasing household debt is a significant global problem, with financial literacy education often proposed as a key solution. This research aims to analyze the influence of socio-economic factors on the effectiveness of financial literacy education in reducing household debt, using a systematic literature review approach to 50 indexed articles. The main findings show that income, education level, employment status, and geographic location significantly influence the success of financial literacy in shaping debt management behavior. The implications of this research provide insight for policy makers and educational institutions to develop financial literacy programs that are more inclusive and responsive to community needs.